2019
DOI: 10.1080/15548627.2019.1647944
|View full text |Cite
|
Sign up to set email alerts
|

A fine-tuning mechanism underlying self-control for autophagy: deSUMOylation of BECN1 by SENP3

Abstract: The roles of SUMOylation and the related enzymes in autophagic regulation are unclear. Based on our previous studies that identified the SUMO2/3-specific peptidase SENP3 as an oxidative stress-responsive molecule, we investigated the correlation between SUMOylation and macroautophagy/autophagy. We found that Senp3 ± mice showed increased autophagy in the liver under basal and fasting conditions, compared to Senp3 +/+ mice. We constructed a liver-specific senp3 knockout mouse; these Senp3deficient liver tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 67 publications
4
54
0
Order By: Relevance
“…In contrast, SUMO-2/3 quickly binds to the substrate under stress conditions, causing a series of defense responses 35,36 . Moreover, the deSUMOylating enzyme SENP3 that specifically targets SUMO2/3 was identified as an oxidative stress-responsive molecule [37][38][39] . SUMO-2/3 modifications can also regulate molecular localization; therefore, in this study we explored whether SUMO-2/3 can affect the subcellular localization of DAXX.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SUMO-2/3 quickly binds to the substrate under stress conditions, causing a series of defense responses 35,36 . Moreover, the deSUMOylating enzyme SENP3 that specifically targets SUMO2/3 was identified as an oxidative stress-responsive molecule [37][38][39] . SUMO-2/3 modifications can also regulate molecular localization; therefore, in this study we explored whether SUMO-2/3 can affect the subcellular localization of DAXX.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, deletion of the Senp3 gene that codes for a de-sumoylating enzyme increased autophagy flux in the liver [148]. These results suggest that SUMOylation promotes autophagy flux.…”
Section: Discussionmentioning
confidence: 77%
“…Cossec et al [ 52 ] revealed that inhibiting SUMO could promote the transformation of ESCs into totipotent 2C-like cells, indicating that SUMO is a key factor in stabilizing cellular pluripotency. Moreover, increasing evidence shows that SUMO is involved in autophagy, for example, the overexpression of the SUMO1 or SUMO2/3 enzyme (SENP3) accelerated the accumulation of autophagosomes [ 53 , 54 ]. Thus, in addition to mTOR, SUMO1 provided further evidence that autophagy was involved in germ cell differentiation from ESCs to SSCs.…”
Section: Discussionmentioning
confidence: 99%